2023
DOI: 10.1177/09721509221145830
|View full text |Cite
|
Sign up to set email alerts
|

Can Individuals with Power Distance Consume Luxury? A Model for Inclusion Through Social Capital and Social Approval

Abstract: This study aims to determine to what extent social capital and social approval mediate the relationship between power distance and purchase intention of luxury brands when these brands are congruent with one’s self. Data were analyzed using structural equation modeling, linear regression to access mediating effects and latent class analysis to profile the sample. Results suggest that social capital and social approval together have a dual mediating effect on consumers’ intention to purchase luxury brands with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…The sophisticated analysis was based on a convenience sample of 196 (mostly undergraduate) students from two universities in Brazil, but neither their specific locational context nor relevant sociological aspects of Brazil as the setting for the research were discussed at any point. The authors do reflect on the possibility that “there might be context-dependent variables that could change the effects we found” (Bizarrias et al , 2023, p. 16) and suggest that qualitative research on the same topic could deliver a more “open” perspective (Bizarrias et al , 2023, p. 16). In contrast, Jiang et al (2021) did at least reflect on the way that contextual specificity makes it difficult to extrapolate findings to wider contexts:…”
Section: The Current State Of Luxury Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…The sophisticated analysis was based on a convenience sample of 196 (mostly undergraduate) students from two universities in Brazil, but neither their specific locational context nor relevant sociological aspects of Brazil as the setting for the research were discussed at any point. The authors do reflect on the possibility that “there might be context-dependent variables that could change the effects we found” (Bizarrias et al , 2023, p. 16) and suggest that qualitative research on the same topic could deliver a more “open” perspective (Bizarrias et al , 2023, p. 16). In contrast, Jiang et al (2021) did at least reflect on the way that contextual specificity makes it difficult to extrapolate findings to wider contexts:…”
Section: The Current State Of Luxury Researchmentioning
confidence: 99%
“…This demonstrates poorly nuanced contextual understanding. Bizarrias et al (2023) looked at the luxury consumption potential of underprivileged individuals from a developing country [Brazil], focusing on "[. .…”
Section: Contextualisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al (2020) studied the private label brand relationship with low-status consumers through power distance believes. Bizarrias et al (2023) also investigated how to include low-status consumers, high in power-distance, into the luxury consumption market. They found that social approval and social capital dual mediating mechanism is capable to insert low-status consumers into sophisticated consumption.…”
Section: Introductionmentioning
confidence: 99%